2021
DOI: 10.33394/jk.v7i3.3329
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Kesalahan Mahasiswa Dalam Menyelesaikan Masalah Matematika (Studi Kasus Masalah Segitiga Pada Mata Kuliah Trigonometri)

Abstract: This study aims to describe mistakes made by first-semester students in solving triangle problems in trigonometry subjects. This research was a qualitative descriptive study with a case study approach. The subjects of this study were students of the first semester of the mathematics education study program at a tertiary institution in the city of Malang. The research instrument consisted of a question about solving triangular problems in the context of trigonometry and an interview guide. The data collected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
3
0
3
Order By: Relevance
“…The results showed that the errors of the first semester students in solving the problem of applying the radian measurement consisted of misconception and factual errors. The results of this research are in accordance with the results of previous researches which showed that students experienced misconceptions and also errors in facts in solving trigonometry problems (Gür, 2009;Hidayat & Aripin, 2020;Imelda, 2018;Jaelani, 2017;Nabie et al, 2018;Setiawan, 2021cSetiawan, , 2021aSetiawan, , 2021bSetiawan, , 2021d.…”
Section: Types Of Errors Error Descriptionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results showed that the errors of the first semester students in solving the problem of applying the radian measurement consisted of misconception and factual errors. The results of this research are in accordance with the results of previous researches which showed that students experienced misconceptions and also errors in facts in solving trigonometry problems (Gür, 2009;Hidayat & Aripin, 2020;Imelda, 2018;Jaelani, 2017;Nabie et al, 2018;Setiawan, 2021cSetiawan, , 2021aSetiawan, , 2021bSetiawan, , 2021d.…”
Section: Types Of Errors Error Descriptionsupporting
confidence: 91%
“…The results also showed that students experienced arithmetic errors in determining the integral of trigonometric functions (Christinove & Mampouw, 2019). The results of the latest research also show that students still experience misconception, arithmetic errors, principle errors, and factual errors in determining the value of trigonometric functions of special angles, quadrant angles, non-acute angles, and triangular problems (Setiawan, 2021a(Setiawan, , 2021d(Setiawan, , 2021b(Setiawan, , 2021c. The results of other research also show that students experience conceptual and principle errors in solving angular velocity problems (Setiawan, 2021e).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Metodologi penelitian yang digunakan adalah kualitatif dengan pendekatan yudiris normatif dengan studi pustaka (Supriyono & Irawan, 2022). Studi pustaka dilakukan untuk mendapatkan berbagai informasi yang relevan dengan topic atau masalah yang sedang diteliti, informasi tersebut dapat diperoleh dari buku-buku ilmiah, laporan penelitian, karangan-karangan ilmiah, buku tahunan, ensiklopedia dan sumber-sumberr tertulis, baik cetak maupun elektronik lainnya (Samhis Setiawan, 2023).…”
Section: Metode Penelitianunclassified